PERAN PENDIDIKAN PROFESI GURU DALAM MENINGKATKAN PROFESIONALITAS DAN KUALITAS PEMBELAJARAN DI INDONESIA - Adelia, Javiarma; Yuniati, Suci; Kurniati, Annisah; Rahmi, Depriwanah (PREDIKSI (PROFESI PENDIDIKAN INDONESIA), 2024)
This research aims to examine how PPG contributes to better teaching practices and student achievement. Studying existing literature is the research approach used. In order to ensure that undergraduates and graduates from fields other than education fully acquire the competences necessary to be effective teachers, PPG has been designed to provide them with the necessary training. Teachers' pedagogical ability, subject knowledge, management abilities, and professional attitudes are all positively impacted by PPG, according to the study's findings. By using efficient learning strategies, incorporating technology, and conducting thorough evaluations, PPG also significantly contributes to raising the bar for educational quality.Keywords : Teacher Professional Education, Teacher Professionalism, Learning Quality